Digitalization for SME: The Impact of the Use of E-Commerce and Fintech on Income Performance - Wulandari, Lucia Putri; Muzakki , Kafidin; Anwar, Chairil; Wicaksono , Achmad (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to describe the impact of e-commerce and fintech use on the background income of snack SMEs. The method used in this study is Qualitative. The object of this research includes the e-commerce and fintech platforms used, while the research subjects consist of MSME owners, financial staff, and marketing staff. The data collection techniques used in this study are observation, interview, documentation, and triangulation techniques. The results of this study show that revenue from conventional methods only accounts for 10% of total revenue, but after switching to using TikTokshop, Shopee, and Lazada as marketing tools, revenue from TikTokshop has increased by 80%, Shopee (20%), and Lazada (5%). This shows that using e-commerce has a higher impact on increasing income. Meanwhile, fintech shows that Dana and ShopeePay contribute around 25%. Compared to cash payments in stores of around 10% with the set strategy, it has a greater impact on increasing the income of SME.